Development of the HBV-TEC hydrological model - Calvo-Valverde, Luis Alexánder; Méndez-Morales, Maikel (Elsevier, 2016)
In this paper, the HBV-TEC hydrological model is presented. The development of this model version, aims to provide researchers and scholars with a stable and robust implementation of the HBV hydrological model based on the R programming language. To evaluate its performance, the HBV-TEC model was applied to three subcatchments of the Aguacaliente river catchment, an experimental catchment located in the province of Cartago, Costa Rica. Results suggest a satisfactory performance of the model for two subcatchments and an unsatisfactory performance of the remaining subcatchment; most of which could be attributed to unsufficient meteorological data along with a highly heterogeneous spatial rainfall-distribution.
Conferencia
Keywords: Calibración; Validación; Rendimiento; Cuencas; Metrología; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Water engineering